Agrobiodiversity in the floodplains and its economic function in the Peruvian Amazon - Rios Arévalo, Michelly (2016)
The aim of the article is to study the sustainable practice and the economic role of the agricultural biodiversity in the more unstable environments of the floodplains, the "sand bars" and "silt bars". The study was carried out in seven communities of the "Setor Muyuy" near the town of Iquitos in 2004. This study also compares the agrobiodiversity of a community in 1999. The methodology used is the same applied by the "People, Land Management and Environmental Change" from United Nations University, which prioritizes experimentation, demonstration and explication of the agricultural systems by farmers themselves. The results show the agricultural systems of sand bars and silt bars vary according to the type of annual sediment. In 2004, agricultural credit is promoted for rice. The agricultural biodiversity in sand bars and silt bars comprised 9 cultures in 1999 and 2 cultures in 2004. The diversity increases among cultures inundated by the river, generating an environment of protection and food for different fish and turtles. The agricultural system have strategies for the minimization of the risk of "river pulse", generally with species cultivated have a short vegetative in the areas of greatest risk of flooding. Finally, the economic role of agricultural biodiversity is aimed for consumption and commercialization. The aquatic diversity generates a complementary economy for the agricultural workers.